ÇALIŞAN KALPTE KORONER BY-PASS CERRAHİSİNİN ÇOK DAMAR HASTALARINDA KULLANIMI - ÖZCAN, Vural; KÖKSAL, Cengiz; SARIKAYA, Sabit; BUĞRA, Onursal; ZENGİN, Mustafa (Cerrahpaşa Medical Journal, 2014)
Background and Desing.- Coronary artery bypass grafting (CABG) with off-pump technique is a widely used treatment modality for coronary artery disease, which avoids the disadvantages of cardiopulmonary bypass (CPB). At the early periods, it was only used for single vessel disease and for patients with low risk. However, currently it became easily applicable to multi-vessel disease and high-risk patients. Material and Methods.- In our clinic, between 2002-2004, 149 patients were underwent CABG, in which 40 of them were high risk. In the high-risk group, 14 patients were diagnosed to have triple or more vessel disease and scheduled for coronary artery bypass grafting with off-pump technique (OPCAB). 11 of them had OPCAB for multi-vessel coronary artery disease. One patient was died in the early postoperative period and one patient had prolonged hospitalization period due to sternal dehiscence. In 3 patients from the OPCAB scheduled group, the operation technique had to be converted to on-pump from off-pump due to hemodynamic problems. Result.- CABG with off-pump technique decreases early postoperative mortality in high-risk patient groups. With the advent of new technologies for cardiac stabilization and positioning, OPCAB technique will be more and more applicable to all patients for myocardial revascularization.